Galatians : A Pentecostal Commentary - Fee, Gordon, (Pentecostal Commentary Series ;, 2007)
An introduction situating Paul's letter in time and space is followed by a detailed discussion of each section of the letter, verse-by-verse commentary, and a theological discussion with challenging questions for individual or group study. This title was granted the 2009 Award of Excellence by the Foundation for Pentecostal Scholarship.